Building a virtual community of practice of researchers in Open and Distance Learning (ODL): an exploratory study - Morgado, Lina (2020)
This article describes a study focused on a group of researchers from a Portuguese Higher ducation Research Center (R&DU). We wanted to see if these researchers considered themselves a community of learning, of practice, or of any type, emerging from the use of virtual environments. We conducted an exploratory qualitative study, integrated in a broader research. We started by making a reflection on the concepts of new forms of learning that are currently breaking out in the network. We then conducted a survey doing semi-structured interviews with a limited group of peers, in order to create an instrument to validate the premise that a group of researchers may function as a learning community or a community of practice. Results showed that the researchers highlighted the importance of interaction and involvement with the Center activities, the lack of alignment between peers and projects, and the need to create the conditions for their functioning as a community. With the results from the interview, we identified some areas for future work, like the need to create a digital platform to foster the needs of a virtual learning and sharing.